H9N2 Viruses Isolated From Mammals Replicated in Mice at Higher Levels Than Avian-Origin Viruses - Sun, Haiwei; Wang, Kai; Yao, Wei; Liu, Qinfang; Yang, Jianmei; Teng, Qiaoyang; Li, Xuesong; Li, Zejun; Chen, Hongjun (Frontiers in Microbiology, 2019)
H9N2 subtype influenza A virus (IAV) has more than 20 genotypes, which can cross species barriers and expand its host range from birds to mammals, even to human. To better understand the impact of different H9N2 genotypes and their characteristics, five H9N2 viruses isolated from different hosts and representing B69 genotype (JS4529，AH120 and MC01), B35 genotype (C1) and G9 genotype (W1) were chosen to determine their replication and pathogenicity in mice and chicken. The results revealed the five H9N2 viruses could leading to clinical diseases in mice and chicken. However, five virus except JS4539 could replicate well in mice and chicken. During the infection, remarkable increases of pro-inflammatory cytokines was positively correlated with viral load in the lung of mice lung. Our data indicated that no significant relationship was found between genotypes and pathotypes for H9N2 viruses.